Дыхание горячих дней: [Вьетнам, Чили, Никарагуа : фотоальбом / И. С. Глазунов - Глазунов Илья Сергеевич (Планета, 1985)
Экземпляры: ИСК (20111031) / Инвентарный номер: 865806 / Цена: 7.50 / Сис.шифр: 85.143(2)7-8 / Авт.знак: Г 52 / ГРНТИ: 18 / ББК: 85.143(2)7-8